Can the Taylor rules explain exchange rate movements? Evidence from Central and Eastern European Countries - Chi-Wei Su; Deng-kui Si; Hsu-Ling Chang; Xiao-Lin Li (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
This study investigates whether the Taylor rules can explain exchange rates for ten Central and Eastern European countries of the conditional distribution by employing a nonlinear quantile stationary test with the Fourier function, which combines the quantile unit root test with smooth unknown multiple breaks through the Fourier function and thus provide more accurate analysis results. We find that the choices and effectiveness of the monetary policies in Central Eastern European economies are highly influenced by the Taylor rules, and also influenced by external factors originating from the United States. Also, our findings point out the bilateral real exchange rates based on Taylor the rules convergence follow a non-linear way. Our results have important policy implications for Central and Eastern European Countries
Argumenta Oeconomica, 2018, Nr 2 (41), s. 35-60
Keywords: Taylor rules; quantile unit root with Fourier function; structural change; trend breaks